Análise de manifestações patológicas em sistemas prediais hidráulicos e sanitários pelos métodos de lichtenstein e gut: estudo de caso na cidade de Apodi-RN - Salgado, Pedro Renato Moraes (Universidade Federal Rural do Semi-Árido, 2018)
The pathology of buildings is the science that studies the failures and the constructive defects that constructions present. Consisting of installations for cold water, hot water, sewage and rainwater, the hydraulic and sanitary building system is one of those that comes into direct contact with users and its malfunction can damage the sanitary security and the well-being of the residents. The objective of this study was to diagnose the pathological manifestations of water and sanitation found in residences located in neighborhoods considered to be the most needy, as well as to propose technical solutions. At the beginning, several technical visits were made to the selection of ten residences that presented pathologies. With the help of the Lichtenstein methods and the GUT matrix, it was possible to organize them in order of priority and then to propose the appropriate solutions. In this study, seven different types of pathologies were diagnosed, such as absence of siphon, poor drainage of the gutter, lack of sewage pipe, rupture of the pipe, exposed sewage pipe, exposed grease box and piping leakage. To determine the order of priority for the pathological manifestations found a GUT matrix was elaborated and for each pathological manifestation technical solutions were presented ranging from the installation of a siphon to modifications in the sanitary facilities, aiming the well being and the health of the residents.
Monografia
Keywords: Patologias em edificações; Instalações hidráulicas; Instalações sanitárias; ENGENHARIAS::ENGENHARIA CIVIL